2013
DOI: 10.5550/sgia.130902.en.006p
|View full text |Cite
|
Sign up to set email alerts
|

Level of Sprint and Jump Abilities and Intermittent Endurance of Elite Young Soccer Players at Different Positions

Abstract: The aim of the study was to analyse a level of sprint abilities, jump abilities and intermittent endurance of playing groups divided according to playing positions (goalkeepers, defenders, midfielders, forwards) from Slovak national under-21 soccer team (N=18, goalkeepers n=2, defenders n=4, midfielders n=7, forwards n=5) in time of qualification for the UEFA European Under-21 Football Championship 2011. The level of sprint abilities was diagnosed with the device Fitro Light Gates (FiTRONIC, Bratislava, The Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…I agree with Pivovarniček et al (2014), the diagnostic of motor abilities could be a decisive factor in the level of the individual, particularly limitation of movement abilities, for coaches and realization teams of sports teams. On the other hand, even an excellent level of motor abilities is not automatically reflected in the individual game performance and game performance teams.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…I agree with Pivovarniček et al (2014), the diagnostic of motor abilities could be a decisive factor in the level of the individual, particularly limitation of movement abilities, for coaches and realization teams of sports teams. On the other hand, even an excellent level of motor abilities is not automatically reflected in the individual game performance and game performance teams.…”
Section: Discussionsupporting
confidence: 63%
“…As Pivovarniček et al (2014), we concluded that the issue of the level of the speed abilities in terms of players' positions could be slave indicators in monitoring and interpreting success in different game situations, for example game situation forward -defender. One of the limiting factors in ice hockey is a sufficient level of speed-power abilities, as reflected in the acceleration of the player in shooting in tackles and in other activities (Kabát & Vanderka, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Podobne ako Pivovarniček et al (2014) sme dospeli k záveru, že problematika úrovne rýchlostných schopností z hľadiska hráčskych postov môže byť pomocným indikátorom pri sledovaní a interpretácii úspešnosti v rôznych herných situáciách, napr. herná situácia útočník -obranca alebo opačne.…”
Section: Diskuseunclassified
“…Súhlasíme s Duthie et al (2006), že akcelerácia je v tímových športoch dôležitá. Rovnako ako vo futbale vysoká úroveň rýchlostných schopností špeciálne akceleračného charakteru vytvára väčší predpoklad získania puku skôr ako protihráč, čím má pod kontrolou hernú situáciu a ďalší vývoj hry (Pivovarniček et al, 2014).…”
Section: Diskuseunclassified